2019
DOI: 10.3389/fphys.2019.00551
|View full text |Cite
|
Sign up to set email alerts
|

A Mucin-Like Protein Is Essential for Oviposition in Nilaparvata lugens

Abstract: Mucins play a variety of roles; for example, in vertebrates, mucins lubricate epithelial surfaces and protect tissue from physical and biological damage, however, knowledge of insect mucins is limited. Here, we identified an eggshell-related mucin-like protein, NlESMuc, in the brown planthopper (BPH), Nilaparvata lugens . NlESMuc was specifically expressed in the follicular cells from the egg chambers of the ovarioles. RNA interference (RNAi) was used to perform fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Although mammalian mucins have been extensively characterized, insect mucins remain largely unknown (Lou et al 2019). Identifying insect mucins by homology search with mammalian mucins could barely work, because of poor sequence conservation (Lang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although mammalian mucins have been extensively characterized, insect mucins remain largely unknown (Lou et al 2019). Identifying insect mucins by homology search with mammalian mucins could barely work, because of poor sequence conservation (Lang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while transcriptional upregulation of the mucin genes in the fat body and ovary is significant, transcriptional regulation of mucins in the midgut is relatively minor. Previous studies showed that the mucin-like protein of Nilaparvata lugens is essential for oviposition (Lou et al 2019), suggesting that some mosquito mucins might have effects on mosquito egg formation and oviposition. One possible explanation for the minor transcriptional regulation of mosquito midgut mucins is that the mucins might be regulated at the translational level or post-translational level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the zona pellucida proteins consist of three or four glycoproteins (ZP1-4) with different functions during oogenesis, fertilization, and early embryonic stage. It is believed that oligosaccharides of these glycoproteins play a key role in the recognition of sperm 34 . In this study, zona pellucida glycoprotein 1 (U3KC80 FICAL) was also identified in the VM of blackbird eggs.…”
Section: Vm Proteinmentioning
confidence: 99%
“…In N. lugens , some progress has been made in understanding its reproductive regulation mechanisms. A mucin-like gene and an eggshell-associated NlChP38 gene, specifically expressed in the follicular cells, are essential for N. lugens oviposition [ 5 , 6 ]. We speculate that there are functional candidate genes contributing to oviposition success, but which remain unexplored.…”
Section: Introductionmentioning
confidence: 99%